An approach to calculate the J-integral by digital image correlation displacement field measurement - Becker, T; Mostafavi, M; Tait, R; Marrow, T (2012)
This paper presents a combined experimental-numerical technique for the calculation of the J-integral as an area integral in cracked specimens. The proposed technique is based on full-field measurement using digital image correlation (DIC) and the finite element method. The J-integral is probably the most generalised and widely used parameter to quantify the fracture behaviour of both elastic and elastoplastic materials. The proposed technique has the advantage that it does not require crack length measurements nor is it limited to elastic fracture mechanics, provided that only small scale yielding is present. Evaluated are three test geometries; compact tension, three-point bend and the double torsion beam. Possible errors and their magnitude and the limitations of the method are considered. © 2012 Wiley Publishing Ltd.